Rapid detection of aflatoxin M1 residues in market milk in Aswan Province, Egypt and effect of probiotics on its residues concentration - Mohammed Zakaria, Asem; Amin, Yahia Abbas; Khalil, Osama Safwat Fawzy; Abdelhiee, Ehab Yahya; Elkamshishi, Mohammed Morsi (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: The objectives of our study were to determine the presence of Aflatoxin M1 (AFM1) in market milk in Aswan province, Egypt and studying the effect of addition of some strains of probiotics microorganisms on AFM1 level in milk. Materials and Methods: Between July and October 2018, 90 market milk samples (15 Ultra Heat Treated (UHT) , 75 raw) were collected from different dairy shops in Aswan City, Egypt to be examined for AFM1 presence by rapid strip test and the results were confirmed by high-performance liquid chromatography (HPLC). Results: The results revealed that all UHT milk samples were negative, while 37 (49%) raw milk samples were positive for AFM1 residues. All 37 positive milk samples were examined by HPLC to determine the level of AFM1. The results showed that the level of AFM1 ranged between 0.053 and 0.207 with mean ± SE of 0.1003 ± 0.008 ppb. Some probiotics strains were used to determine their effect on AFM1 by milk fermentation; the result showed that the probiotics have significant effect on the reduction of AFM1 level in milk (p < 0.05). Also, Public health importance of AFM1 was discussed. Conclusion: Presence of AFM1 in 49% of examined raw milk samples indicate widespread occurrence of AFM1 in market milk in Aswan province, Egypt which considered possible hazards for consumers, while the absence of AFM1 from UHT milk indicates that type of milk is safer. So, regular monitoring of AFM1 in market milk is necessary for evaluating their contamination status. Mixed starter culture of Lactobacillus bulgaricus and Streptococcus thermophilus could be used as a biological agent for the reduction of AFM1 in milk. J. Adv. Vet. Anim. Res., 6(2): 197-201, June 2019